How inversion variants can shape neural circuitry: Insights from the three-morph mating tactics of ruffs - Loveland, Jasmine L.; Giraldo-Deck, Lina M.; Kelly, Aubrey M. (Frontiers in Physiology, 2022)
Behavior polymorphisms underlying alternative mating tactics can evolve due to genetic inversions, especially when inversions capture sets of genes involved in hormonal regulation. In the three-morph system of the ruff (Calidris pugnax), two alternative morphs (Satellites and Faeders) with distinct behavioral and low circulating testosterone are genetically determined by an inverted region on an autosomal chromosome. Here, we discuss recent findings on the ruff and present novel insights into how an inversion that poses drastic constraints on testosterone production might lead to morph-specific differences in brain areas that regulate social behavior. A gene responsible for converting testosterone to androstenedione (HSD17B2) is located inside the inverted region and is a promising candidate. We identify a single missense mutation in the HSD17B2 gene of inverted alleles that is responsible for a 350-500% increase in testosterone to androstenedione conversion, when mutated in the human HSD17B2 protein. We discuss new evidence of morph differences in neural HSD17B2 expression in embryos and circulating androgens in sexually-immature juveniles. We suggest processes that shape morph differences in behavior likely begin early in ontogeny. We propose that the organization of behaviorally relevant neuron cell types that are canonically sexually dimorphic, such as subpopulations of aromatase and vasotocin neurons, should be particularly affected due to the life-long condition of low circulating testosterone in inversion morphs. We further emphasize how HSD17B2 catalytic activity extends beyond androgens, and includes estradiol oxidation into estrone and progesterone synthesis. Lastly, we underscore dimerization of HSD17B2 as an additional layer of complexity that merits consideration.